A NEED ANALYSIS OF JUNIOR HIGH SCHOOL ENGLISH TEACHERS IN BIMA TO EMPOWER THEIR TEACHING PERFORMANCE - Nurnaningsih Nurnaningsih (UAD TEFL International Conference)
This research focuses on analysis English teachers needs to empower their teaching performance particularly in the context of Bima, West Nusa Tenggara. This research aimed to find out the particular needs of Junior High School teachers in Bima to develop their professionalism. The data of this study were collected through several techniques such as questionnaires, interviews, observations, and documents. The data of this study was analyzed qualitatively. Several aspects related to the teachers` performance and teachers` beliefs are discussed in this study. The finding of this study shows that teachers in Bima find a lot of barriers in their teaching performance related to the lack of teaching media, infrastructures, students` low motivation, teachers` limits, and so on. Some of English teachers in Bima believe that they need a routine in-service training program to unify their perspective on respect to optimize their role as English teachers. Considering the critical need of teacher training activity, some of English teachers in Bima agreed to run an autonomous MGMP program for once a month regular meeting. This study offers some suggestions for Junior High School English teachers particularly in the context of Bima as the location of the study. By the presented facts, hopefully English teachers in Bima get such information which benefits to empower their teaching performance.